2004
DOI: 10.1091/mbc.e03-08-0620
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PALS1 Expression Leads to Tight Junction and Polarity Defects

Abstract: Prior work in our laboratory established a connection between the PALS1/PATJ/CRB3 and Par6/Par3/aPKC protein complexes at the tight junction of mammalian epithelial cells. Utilizing a stable small interfering RNA expression system, we have markedly reduced expression of the tight junction-associated protein PALS1 in MDCKII cells. The loss of PALS1 resulted in a corresponding loss of expression of PATJ, a known binding partner of PALS1, but had no effect on the expression of CRB3. However, the absence of PALS1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
183
1
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(221 citation statements)
references
References 38 publications
25
183
1
10
Order By: Relevance
“…Lysates were cleared by centrifugation (12,000 ϫ g for 15 min at 4°C). Western blotting was performed as described previously (Straight et al, 2004).…”
Section: Immunoblottingmentioning
confidence: 99%
See 3 more Smart Citations
“…Lysates were cleared by centrifugation (12,000 ϫ g for 15 min at 4°C). Western blotting was performed as described previously (Straight et al, 2004).…”
Section: Immunoblottingmentioning
confidence: 99%
“…Prior work in our laboratory showed that when the expression of the tight junction-associated protein PALS1 is markedly reduced in MDCKII cells by SiRNA expression, the expression level of PATJ is lowered accordingly, and the formation of tight junctions is significantly delayed (Straight et al, 2004). To further investigate the role of PALS1 in junction formation, we designed two canine-specific SiRNA sequences and created PALS1 KD cell lines by stably expressing the SiRNA-encoding plasmid in MDCKII cells.…”
Section: Depletion Of Pals1 Disrupts Both Tight Junctions and Adherenmentioning
confidence: 99%
See 2 more Smart Citations
“…PATJ se lie également à Pals1 (protein associated with Lin-7, homologue de Sdt), une MAGUK localisée dans les jonctions serrées, et peut donc se lier potentiellement à d'autres protéines ayant un rôle à jouer dans l'organisation de la région apicale des jonctions [34]. La perte d'expression de Pals1 perturbe l'établis-sement des jonctions serrées, indiquant que ce complexe de protéines est important pour ce processus [35]. CRB3 est exprimé par la majorité des épithéliums et sa surexpression entraîne aussi un défaut de formation des jonctions serrées [36,37].…”
Section: Les Complexes Importants Pour La Polarité éPithéliale Sont Cunclassified